(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Due to the rapid growth of ICT, online education has become increasingly significant in higher education. This study investigates how professors feel about online education and how it impacts students’ grades. The mixed-method approach included surveying 150 undergraduate and graduate students using structured questionnaires for quantitative data and interviewing 20 faculty members for qualitative data. Even while online platforms make learning more flexible and accessible, the findings show that they still have several issues, including a lack of training, technical barriers, less interaction, and apathy. Most students preferred online platforms to institutional institutions, emphasizing the role of technology in encouraging independence and academic performance. Faculty say effective online training takes substantial preparation, new ideas, and continual professional development. Despite its limitations, online learning may improve students’ skill development and knowledge acquisition with the correct infrastructure and technique. The study suggests improving digital literacy, institutional platforms, and student-centered teaching to promote higher education online learning.